ASUPAN ZAT GIZI DAN ANEMIA PADA REMAJA PUTRI DI SALAH SATU SLTP KOTA PEKANBARU - ernalia, Yanti; Tamba, Lusiana (JURNAL MEDIA KESEHATAN, 2019)
Anaemia is an important nutritional problems in Indonesia, including in Pekanbaru City in Riau Province. There is a relationship between nutrient intake with the incidence of anemia in young women. The study aimed to determine the incidence of anemia in female students at one of the junior high schools in Pekanbaru, as well as in relation to nutrient intake. The study was observational with cross sectional design. Samples consisted of adolescence of 57 student junior high school between 11-15 years old with Purposive Sampling Technique. Data of consumption were obtained from food recall, and data of anaemia were obtained by hemocue with digital hemoglobinometry. The collected data were process and analyzed using univariate and bivariate. There are 11 subjects (19.3%) who suffered from anemia. Most of adolescents had a deficiency in protein, iron, folic acid, and vitamin B12 consumption. The result of statistical test showed there was no significant difference in average intake of protein, iron, folic acid ,and vitamin B12, between anaemia and non anaemia adolescents (p>0.05). There was relationship between protein intake and anaemia (p=0. 041). Low intake of protein was risk factors of the anaemia incidence in female students at one of the junior high schools in Pekanbaru. Detection of nutritional status (dietary behavior) is needed to protect the incidence of anaemia of adolescent girls, and increased nutrition intake of adolescents through information, communication, and nutrition education.